Ancient Christianity in Cyberspace: A Digital Media Lab for Students. - Royalty, Robert M. (Teaching Theology & Religion, 2002)
“Ancient Christianity, Ancient Cities – and Cyberspace?” was a teaching experiment combining the study of theology, religion, history, and new computer technologies. The course included both a regular class meeting and a concurrent digital media lab. All student assignments were digital. Students came in with a wide variety of technical knowledge and backgrounds in classical and religious studies. In addition to learning about the history and theology of early Christianity, students became critical learners of technology within the ideal of a liberal arts education.